The cytoprotective effects of endogenous activated protein C reduce activation of coagulation during murine pneumococcal pneumonia and sepsis - Schouten, Marcel; van ‘t Veer, Cornelis; Poulussen, Nadia; Meijers, Joost C.M.; Levi, Marcel; Esmon, Charles T.; van der Poll, Tom (Thrombosis research, 2015)
Streptococcus (S.) pneumoniae is the most common causative pathogen in community-acquired pneumonia and sepsis. Activated protein C (APC) has been implicated as an important anticoagulant and anti-inflammatory mediator. We here sought to determine the role of the anticoagulant and cytoprotective functions of endogenous APC during pneumonia and sepsis caused by S. pneumoniae. Mice were treated intraperitoneally with monoclonal antibody (mAb) 1609 (which inhibits both anticoagulant and cytoprotective effects of APC), mAb 1591 (which inhibits only the anticoagulant effects of APC) or a control antibody mAb prior to infection with viable S. pneumoniae via the airways (to induce pneumonia) or via the tail vein (to induce primary sepsis). Mice were analyzed at 24 or 48hours after infection. mAb 1609, but not mAb 1591, enhanced the procoagulant response to pneumococcal pneumonia and sepsis, as indicated by elevated levels of thrombin-antithrombin complexes and D-dimer in plasma and lungs. mAb 1609 only modestly affected the fibrinolytic response (elevated plasma and lung levels of the fibrinolysis inhibitor plasminogen activator inhibitor type I during sepsis) and cytokine release (elevated plasma interleukin-6 concentrations during pneumonia). The cytoprotective effects of endogenous APC reduce activation of coagulation during murine pneumococcal pneumonia and sepsis. •Endogenous PC inhibits pulmonary and systemic coagulation in pneumococcal infection.•The cytoprotective effects of APC inhibit coagulation in pneumococcal infection.•Endogenous APC has small impact on fibrinolysis in pneumococcal infection.•Endogenous APC has small impact on inflammation in pneumococcal infection.